EXPLORING LEARNERS’ AUTONOMY IN ONLINE LANGUAGE-LEARNING IN STAI SUFYAN TSAURI MAJENANG - Pipit Muliyah; Dyah Aminatun; Sukma Septian Nasution; Tommy Hastomo; Setiana Sri Wahyuni Sitepu; Tryana (Getsempena English Education Journal, 2020)
The impact of the coronavirus outbreak on the education system is inevitable that higher education institutions choose to transform their instructional practices to entirely online using specific platforms. This shifting comes with challenges to students as they are demanded to be independent and autonomous. This study investigated the students’ readiness and perception towards being an autonomous learner in online language-learning. This case study investigated 25 students who joined online language learning by the WhatApps group in an English department of STAI Sufyan Tsauri Majenang. The data were gained by giving an online questionnaire, having an online interview with some students who were chosen randomly, and also assigning students self-report. The data showed that the students do not have enough autonomy in online language-learning. It means that the students are not ready to be autonomous learners in online language learning. The result of the study indicated that the students prefer having a face to face class and direct guidance from the teacher where 66.9% of the same students prefer learning in class or face to face meeting. In comparison, only 18.5 % who share no problem having an online class. 14.6% of them enjoy both options. This finding suggests that teachers need some strategies to promote and foster students’ learner autonomy to achieve learning objectives in online language learning.